Survey of the incidence and distribution of viruses infecting yam (Dioscorea spp.) in Ghana and Togo - Eni, A.O.; Hughes, Jacqueline d'Arros; Asiedu, Robert; Rey, M.E.C. (2010)
Yam leaves were collected during surveys of major yam producing agro-ecological zones (AEZs) in Ghana (n = 628) and Togo (n = 218) respectively, in 2005. Leaf tissues were tested for Cucumber mosaic virus (CMV), Dioscorea mottle virus (DMoV), Yam mild mosaic virus (YMMV), Yam mosaic virus (YMV) and badnaviruses by enzyme-linked immunosorbent assay (ELISA), immunocapture-polymerase chain reaction (IC-PCR) and/or IC-reverse transcription-PCR (IC-RT-PCR). Eighty-one percent (370/459) and 78.9% (127/161) of symptomatic leaf samples from Ghana and Togo, respectively and 56.2% (95/169) and 57.9% (33/57) of non-symptomatic leaf samples, reacted positive to CMV, YMMV, YMV and/or badnaviruses, but DMoV was not detected. The highest incidence of YMV and badnaviruses was observed in the forest–savannah transition and Guinea savannah AEZ respectively in Ghana. In Togo, incidence of badnaviruses across the four AEZ ranged from 50 to 57.9%; however, Savane Derivée Seche AEZ had the highest incidence of badnaviruses (57.9%), YMV (34.2%) and CMV (7.9%). Mixed infection of badnaviruses and YMMV was the most frequent (105 of 276 mixed infections) in the two countries and Dioscorea alata was more heavily infected than D. rotundata in both countries.